(untitled) (Research, Society and Development, 2023)
The study intends to analyze, through this review, the efficacy of PARP inhibitor drugs, based on the following criteria: overall survival (OS), progression-free survival (PFS), toxicity and tolerability (adverse events (AEs) presented by patients). This study consists of a systematic review of the literature about the effectiveness of PARP inhibitor drugs, through data from OS, PFS and AEs presented. The systematic review was based on the methodological guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and the guiding question of the study was established through an acronym defined as PICO, that is, Population, Intervention/Exposure, Comparison and “Outcome”. We included studies that contained all investigator-defined efficacy data and that compared therapy with i-PARP and without i-PARP. Seven articles were included that contained OS, PFS and EA data and that compared i-PAPR dose or drug regimens. Three of the seven studies looked at the efficacy of the Gemcitabine + Carboplatin + Iniparib regimen and demonstrated that the addition of Iniparib had a significant effect on efficacy. Two other studies showed good results with the combination of other drugs with i-PARP Olaparib. The studies included in this review corroborate the use of i-PARPs, mainly Iniparib and Olaparib, together with conventional chemotherapy demonstrating efficacy for TNBC.